Acute Triangulations of the Cuboctahedral Surface - Feng, Xiao; Yuan, Liping (Computational Geometry, Graphs and Applications, 2011)
In this paper we prove that the surface of the cuboctahedron can be triangulated into 8 non-obtuse triangles and 12 acute triangles. Furthermore, we show that both bounds are the best possible.